2016
DOI: 10.1108/tldr-06-2016-0016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the costs and cost-effectiveness of interventions for people with learning disabilities and behaviour that challenges: the need to improve the evidence base

Abstract: The purpose of this paper is to provide a commentary on the challenges associated with evaluating the costs and cost-effectiveness of interventions for people with learning disabilities and behaviour that challenges. Design/methodology/approach The paper is a commentary on a range of evidence relating to the findings of "Positive behavioural support for children and adolescents with learning disabilities: an initial exploration of service and costs". Specific attention is paid to gaps in the literature and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…This is the first RCT that we are aware of to conduct an extensive cost-effectiveness analysis of a PBS-related intervention, with most studies in this area predominantly using a before-and-after design. 19 Whereas before-and-after studies have hypothesised a decrease in accommodation costs for participants who are provided with PBS, this study has echoed the findings of other economic evaluations of person-centred interventions for participants with challenging behaviour in that there is no reduction in costs. 16 This is likely to be because of changes in community care for people with challenging behaviour and ID, which require significant changes in the commissioning of appropriate services, therefore taking time to implement fully.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This is the first RCT that we are aware of to conduct an extensive cost-effectiveness analysis of a PBS-related intervention, with most studies in this area predominantly using a before-and-after design. 19 Whereas before-and-after studies have hypothesised a decrease in accommodation costs for participants who are provided with PBS, this study has echoed the findings of other economic evaluations of person-centred interventions for participants with challenging behaviour in that there is no reduction in costs. 16 This is likely to be because of changes in community care for people with challenging behaviour and ID, which require significant changes in the commissioning of appropriate services, therefore taking time to implement fully.…”
Section: Discussionsupporting
confidence: 54%
“…The presence of challenging behaviour increases the cost of care for people with ID, mostly due to increases in support and long-term inpatient care, often in expensive out-of-area placement; [14][15][16][17] and also increases family-carer burden. 18 Hunter 19 argues that the limited economic data currently available make use of information based on services that are many years old and superseded by advances in community health and social care.…”
Section: Cost Of Challenging Behaviour To Societymentioning
confidence: 99%
“…10,29 The evidence for the cost-effectiveness of PBS and other interventions for behaviours that challenge in adults with intellectual disability are limited, particularly economic evaluations that include both costs and QALY. 9,30 One pilot RCT of a specialist service delivering applied behavioural analysis (ABA) in one area in England 31 found a significant difference in ABC-C total and domain scores in the intervention arm at 6 months. Service use showed that ABA on average reduced the costs by £2900 per participant compared with TAU (95% CI −£6788 to 987).…”
Section: Discussionmentioning
confidence: 99%
“…7 Although previous studies have found significant associations between degree of intellectual disability, behaviours that challenge and service costs, 3,6,8 these are based on small observational studies or localised examples of services that may not apply in other parts of the UK or having been superseded by advances in community health and social care. 9 Recently, the National Institute for Health and Care Excellence (NICE) recommended that intellectual disability services in England deliver personalised interventions for behaviours that challenge within the framework of a complex intervention, namely PBS. 10 PBS incorporates applied behavioural analysis with the aim of understanding the purpose of an individuals' behaviour and context in which it occurs followed by the development of a personalised support plan ostensibly leading to reduction in such behaviours and improvement in quality of life.…”
mentioning
confidence: 99%
See 1 more Smart Citation